Centrality of Striatal Cholinergic Transmission in Basal Ganglia Function - Bonsi, Paola; Cuomo, Dario; Martella, Giuseppina; Madeo, Graziella; Schirinzi, Tommaso; Puglisi, Francesca; Ponterio, Giulia; Pisani, Antonio (Frontiers in Neuroanatomy, 2011)
Work over the past two decades revealed a previously unexpected role for striatal cholinergic interneurons in the context of basal ganglia function. The recognition that these interneurons are essential in synaptic plasticity and motor learning represents a significant step ahead in deciphering how the striatum processes cortical inputs, and why pathological circumstances cause motor dysfunction. Loss of the reciprocal modulation between dopaminergic inputs and the intrinsic cholinergic innervation within the striatum appears to be the trigger for pathophysiological changes occurring in basal ganglia disorders. Accordingly, there is now compelling evidence showing profound changes in cholinergic markers in these disorders, in particular Parkinson’s disease and dystonia. Based on converging experimental and clinical evidence, we provide an overview of the role of striatal cholinergic transmission in physiological and pathological conditions, in the context of the pathogenesis of movement disorders.